SIMULATION OF CLOSED-LOOP NATURAL CONVECTION USING BUOYANCY SMOOTHED PARTICLE HYDRODYNAMICS - Rendian Septiawan, Reza
Natural convection is a phenomenon that occurred as a consequence of the exis- tence of temperature dierence on the uid. One example of the application of this phenomenon is the coolant system of nuclear reactor which is a closed-loop system that has both hot reservoir and cold reservoir on it. The necessities to nd physical parameters aect the natural convection process arises to make the optimal closed- loop natural convection system. One method that can be used for studying physical parameters that aect the natural convection process is through the simulation. In this thesis we use the SPH simulation method which is particle-based method com- bined with the heat transfer scheme to observe and study the factors that in uencing natural convection process. The result shows that the height dierence and temper- ature dierence from both reservoirs aect the equilibrium speed and time needed to obtain the thermal and mechanical equilibriums.